Characterization of a Novel RNA Polymerase Mutant That Alters DksA Activity - Satory, Dominik (American Society for Microbiology, 2013)
The auxiliary factor DksA is a global transcription regulator and, with the help of ppGpp, controls the nutritional stress response in Escherichia coli. Although the consequences of its modulation of RNA polymerase (RNAP) are becoming better explained, it is still not fully understood how the two proteins interact. We employed a series of genetic suppressor selections to find residues in RNAP that alter its sensitivity to DksA. Our approach allowed us to identify and genetically characterize in vivo three single amino acid substitutions: β′ E677G, β V146F, and β G534D. We demonstrate that the mutation β′ E677G affects the activity of both DksA and its homolog, TraR, but does not affect the action of other secondary interactors, such as GreA or GreB. Our mutants provide insight into how different auxiliary transcription factors interact with RNAP and contribute to our understanding of how different stages of transcription are regulated through the secondary channel of RNAP in vivo.